2015
DOI: 10.24188/recia.v7.n2.2015.261
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento productivo de terneros lactantes suplementados con maíz más torta de algodón en el departamento de Córdoba, Colombia

Abstract: Con el fin de contribuir a la búsqueda de estrategias nutricionales y mejorar la ganancia de peso de terneros en los sistemas pecuarios, se evaluó el comportamiento productivo de terneros lactantes suplementados en un sistema doble propósito. Se utilizaron 40 terneros (20 hembras y 20 machos), de 1 a 30 días de edad y con pesos promedios de 26,5±3,08 kg, los cuales fueron sometidos al manejo de semiconfinamiento y suplementados con una mezcla alimenticia basada en torta de algodón y maíz molido en proporciones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…There were no differences (p0.05) in GDP for females and males, similar to zebu cross-bred calves (Cárdenas et al, 2015); nevertheless, other studies state differences in GDP and weaning weight between sexes (Heras-Torres et al, 2008;Salamanca et al, 2011). CL in LT calves was similar in both shepherding systems (p0.05, Table 2) and at 30.2 kg per day 1 for cross-bred calves fed with one nipple for the first 100 days of life (Chirinos et al, 2011);nevertheless, their GDP was of 28720 g per day d 1 , supplemented with 300 g of concentrated feed (20% PC), lower than the GDP of LT calves.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…There were no differences (p0.05) in GDP for females and males, similar to zebu cross-bred calves (Cárdenas et al, 2015); nevertheless, other studies state differences in GDP and weaning weight between sexes (Heras-Torres et al, 2008;Salamanca et al, 2011). CL in LT calves was similar in both shepherding systems (p0.05, Table 2) and at 30.2 kg per day 1 for cross-bred calves fed with one nipple for the first 100 days of life (Chirinos et al, 2011);nevertheless, their GDP was of 28720 g per day d 1 , supplemented with 300 g of concentrated feed (20% PC), lower than the GDP of LT calves.…”
Section: Methodsmentioning
confidence: 57%
“…Protein and lactose amounts were greater for SSPi related to greater GDP of calves. Rumen begins to become functional at 60 days of life in calves, reason why the daily ingestion of milk is considered to be a diet supplement, capable of favoring greater growth rates (Cárdenas et al, 2015). Martínez et al (2010) found a significant correlation between weight at 210 days and protein present in milk.…”
Section: Methodsmentioning
confidence: 99%
“…Por otro lado, se observa una buena eciencia de los suplementos [EMA, palmiste, salvado de trigo y ensilado de botón de oro] en la ganancia de peso, obteniéndose un valor de conversión promedio en todos los tratamientos de 1:1.025 [Tabla 4]. Este valor de la relación es bastante favorable, lo cual indica que los ovinos respondieron ade-cuadamente a la suplementación en los cuatro tratamientos, con lo cual presentaron una mayor capacidad de consumo de la ración (Cárdenas et al, 2015).…”
Section: Resultados Y Discusiónunclassified
“…Tabla 5: Comportamiento de la Ganancia diaria (Kg/día). Concordado con lo informado por Cardenas, J., et al, (2015) los terneros que son suplementados presentan ganancias diarias de peso promedio mayor con respecto al grupo control. Por tanto, el uso del concentrado comercial pre-inicial con el 25% de proteína en la investigación beneficia a los terneros en la ganancia de peso.…”
Section: Resultados Y Discusiónunclassified